On Soft bc-Open Sets in Soft Topological Spaces - Hameed, Saif Z.; Hussein, Adiya K. (Iraqi Journal of Science, 2020)
In this paper, we offer and study a novel type generalized soft-open sets in topological spaces, named soft Æ„c-open sets. Relationships of this set with other types of generalized soft-open sets are discussed, definitions of soft Æ„ , soft bc- closure and soft bc- interior are introduced, and its properties are investigated. Also, we introduce and explore several characterizations and properties of this type of sets.